Efficient access to enantiomerically pure cyclic α-amino esters through a lipase-catalyzed kinetic resolution - Alatorre-Santamaría, Sergio (2009)
A series of α-amino acid derivatives containing the 2,3-dihydroindole or octahydroindole core have been chemoenzymatically synthesized in good overall yields and high enantiomeric purity under mild reaction conditions using lipases for the introduction of chirality. Candida antarctica lipase type A has shown excellent activity and high enantiodiscrimination ability towards the two cyclic amino esters used as substrates. The selectivity of the process proved to be greatly dependent on the alkoxycarbonylating agent. Thus, the enzymatic kinetic resolution of methyl indoline-2-carboxylate has been successfully achieved using 3-methoxyphenyl allyl carbonate, whereas (2R,3aR,7aR)-benzyl octahydroindole-2-carboxylate required the less reactive diallyl carbonate.